Pattern of Inpatient Consultation-liaison Psychiatry Utility in a Tertiary Care Hospital - Kumar, Pankaj; Chaudhary, Rupesh; Bhalla, Jasleen Kaur; Gupta, Aarti (International journal of applied and basic medical research, 2023)
Background: Consultation-liaison psychiatry (C-LP) is an interface between physical and psychological health where the psychiatrists become a part of the medical team for a holistic approach in the treatment of the patient. Aims: Our study aimed to see the pattern and utility of C-LP services among inpatient referrals to the department of psychiatry. Settings and Design: This observational descriptive study recorded inpatient referrals to the department of psychiatry of a tertiary care hospital for 2 months. Subjects and Methods: The Mini-International Neuropsychiatric Interview (M. I. N. I.) was administered for identifying the comorbid psychiatric diagnoses. Results: Most of the received inpatient referrals were for male patients (73.7%) in the age group of 30-60 years (58%). Overall, the referral rate was significantly higher from the emergency department and intensive care units (ICU) (50%), followed by specialty (medicine and surgery) wards (20%) and super specialty (cardiology, gastroenterology, and oncology) wards (16%). Altered sensorium and restlessness were the most common reasons for referral (42%), followed by alcohol/drug withdrawal (21.6%), somatic complaints (7.3%), sadness of mood, disturbed sleep, and deliberate self-harm (6% each). Substance use disorders, including alcohol and opioid (32%), delirium (25%), and depression (19%), were among the most common psychiatric diagnoses seen in the referred patients. Conclusions: The pattern observed indicates that most inpatient referrals for psychological evaluation are received for altered sensorium from emergency and ICU than wards. The utility of C-LP helps to understand the reciprocal interdependence between the medical illness and the psychiatric comorbidity.